Operative Management of Ulnar Collateral Ligament Insufficiency in Adolescent Athletes. (January 2014) - Jones, Kristofer J.; Dines, Joshua S.; Rebolledo, Brian J.; Weeks, Kenneth D.; Williams, Riley J.; Dines, David M.; Altchek, David W.
Background: The incidence of ulnar collateral ligament (UCL) injuries of the elbow has increased in adolescents over the past decade because of widespread participation in athletics and heightened awareness among physicians. Hypothesis: Ulnar collateral ligament reconstruction using the docking technique would result in a successful return to athletic activity in this age group. Study Design: Case series; Level of evidence, 4. Methods: Study participants were 55 skeletally mature adolescent athletes (mean age, 17.6 years; range, 15-18 years) who underwent UCL reconstruction between 2008 and 2010. While the majority of patients were baseball players (n = 47), there were 3 gymnasts and 5 javelin throwers included in the study. Each patient underwent UCL reconstruction utilizing the docking technique after an adequate trial of nonoperative management (mean, 5.8 months). At the latest follow-up, patients were evaluated to determine their ability to return to athletic activity. Clinical outcomes were classified using the Conway scale, the Andrews-Timmerman score, and the Kerlan-Jobe Orthopaedic Clinic (KJOC) score. Results: At a minimum 2-year follow-up, 87% (48/55) of patients had excellent results using the Conway scale. Overall, there were only 2 poor results (3.6%) that were observed in patients with concomitant osteochondritis dissecans lesions of the capitellum. There were 4 postoperative complications in 4 patients (2 gymnasts and 2 javelin throwers) who developed ulnar neuritis after UCL reconstruction. The mean Andrews-Timmerman score was 83.6 ± 7.2 (range, 30-100), and the mean KJOC score was 88.0 ± 6.0 (range, 40-100). Conclusion: The docking technique results in favorable clinical outcomes in adolescent athletes with UCL insufficiency at a minimum of 2 years postoperatively. Patients with concomitant intra-articular lesions should be cautioned preoperatively that they might experience inferior clinical outcomes. Postoperatively, adolescent gymnasts and javelin throwers may be at an increased risk for transient paresthesia of the ulnar nerve caused by increased stress on the medial elbow.